A RETROSPECTIVE STUDY ON MATERNAL AND FETAL OUTCOMES ASSOCIATED WITH ASSISTED REPRODUCTIVE TECHNOLOGIES - HAQ , W; AWAN , F; TAJ , S; ARSH, DR; BHITTANI , R (Biological and Clinical Sciences Research Journal, 2024)
Assisted Reproductive Technologies (ART) have revolutionized the landscape of reproductive medicine, offering hope to couples facing infertility challenges. The study's main objective is to find the maternal and fetal outcomes associated with assisted reproductive technologies. This retrospective cohort study was conducted in Lady Reading Hospital Peshawar from July 2019 to June 2023. The study includes 850 participants who underwent ART procedures between 2021 and 2022. Details of the ART procedures, such as the technique employed, the number of embryos transferred, and the utilization of preimplantation genetic testing, were meticulously documented. Maternal outcomes were a focal point, with a comprehensive assessment of pregnancy-related hypertensive disorders, gestational diabetes, mode of delivery, and any postpartum complications. Data was collected from 850 participants. The mean maternal age was 33.5 years (SD = 4.2), and the mean BMI was 25.8 (SD = 3.5). The primary causes of infertility varied, with male factor infertility being the most prevalent at 40%, followed by ovulatory dysfunction at 30% and unexplained infertility at 20%. The ART procedures in the study cohort comprised In Vitro Fertilization (IVF) at 60%, followed by Intracytoplasmic Sperm Injection (ICSI) at 25%, and other ART techniques at 15%. Regarding the number of embryos transferred, the majority received a single source (70%), with 20% receiving two starts and 10% receiving three or more. It is concluded that pregnancies conceived through Assisted Reproductive Technologies (ART) exhibit a higher prevalence of pregnancy-related hypertensive disorders and gestational diabetes compared to naturally conceived pregnancies.